CAR and TCR form individual signaling synapses and do not cross-activate, however, can co-operate in T cell activation - Barden, Markus; Holzinger, Astrid; Velas, Lukas; Mezősi-Csaplár, Marianna; Szöőr, Árpád; Vereb, György; Schütz, Gerhard J.; Hombach, Andreas A.; Abken, Hinrich (Frontiers in Immunology, 2023)
In engineered T cells the CAR is co-expressed along with the physiological TCR/CD3 complex, both utilizing the same downstream signaling machinery for T cell activation. It is unresolved whether CAR-mediated T cell activation depends on the presence of the TCR and whether CAR and TCR cross-activate themselves upon engaging their respective antigen. Here we demonstrate that the CD3 CAR level was independent of the TCR associated CD3 and could not replace CD3 to rescue the TCR complex in CD3 KO T cells. Upon activation, the CAR did not induce phosphorylation of TCR associated CD3 and, vice versa, TCR activation did not induce CAR CD3 phosphorylation. Consequently, CAR and TCR did not cross-signal to trigger T cell effector functions. On the membrane level, TCR and CAR formed separate synapses upon antigen engagement as revealed by total internal reflection fluorescence (TIRF) and fast AiryScan microscopy. Upon engaging their respective antigen, however, CAR and TCR could co-operate in triggering effector functions through combinatorial signaling allowing logic “AND” gating in target recognition. Data also imply that tonic TCR signaling can support CAR-mediated T cell activation underlining the potential relevance of the endogenous TCR for maintaining T cell capacities in the long-term.